DEVELOPMENT OF ORALLY DISINTEGRATING TABLETS OF MEMANTINE HYDROCHLORIDE-A REMEDY FOR ALZHEIMER’S DISEASE - GHOGARI, IMRAN S.; JAIN, PRITAM S. (International Journal of Applied Pharmaceutics, 2020)
Objective: The study is directed towards the development of an orally disintegrating drug delivery system of memantine hydrochloride which can be commercially exploited for the well-being of society for the treatment of Alzheimer’s disease, which is a most common form of dementia. Methods: Orally disintegrating immediate-release tablets of memantine hydrochloride were prepared and optimized for disintegration time and in vitro drug release. The top spray granulation method was used for the preparation of granules. Subsequently, these granules were compressed to tablets. The levels of diluent, disintegrant and taste-masking agents were optimized using the design of experiments. The resulting tablets were evaluated for disintegration time and in vitro drug release. The optimized formulation was subjected to accelerated stability study for 3 mo. Results: The optimized orally disintegrating tablet formulation exhibited a disintegration time of 2-3 min and complete drug release i.e. more than 85 % drug release within 10 min while performing in vitro drug release study. This is a prerequisite for faster action in the case of patients suffering from Alzheimer’s disease. Accelerated stability studies indicated good physical and chemical stability of the optimized formulation. Conclusion: Developed orally disintegrating tablet formulation of memantine hydrochloride could release the drug faster compared to conventional immediate-release tablets which is useful in paediatric, geriatric and psychiatric patients.